Answer:
x = 3
y = -2
Explanation:
2x + y = 4; y = x - 5
First name the equation
2x + y = 4 ...(1)
y = x - 5. ...(2)
Now Substitute the value of y in equation (1)
2x + y = 4
2x + (x - 5) = 4
2x + x - 5 = 4
3x = 4 + 5
3x = 9
x = 9 ÷ 3
x = 3
Now, put the value of x = 3 in equation (2)
y = x - 5
y = 3 - 5
y = - 2
Thus, The Value of x is 3 and the value of y is -2
FOR VERIFICATION ONLY:
2x + y = 4
2(3) + (- 2) = 4
6 - 2 = 4
4 = 4
y = x - 5
- 2 = 3 - 5
- 2 = - 2
Hence, L.H.S = R.H.S
-TheUnknownScientist